Transforming Research Landscape in Africa using Open Access: The case of Ethiopia - Tekle, Solomon, Mekonnen (My University, 2019)
The presentation will discuss Ethiopia's open access initiatives as a model to transform the research landscape in Africa mainly focusing on the national open access policy of Ethiopia.
Keywords: Open Access; Africa; Ethiopia